Resistance of frozen-thawed epididymal and ejaculated spermatozoa of buffalo bulls - GUPTA, H P; SAHNI, K L; MOHAN, G (The Indian Journal of Animal Reproduction, 2023)
Storage and thermal resistance (per cent motile sperm at 5°C and 37°C, respectively) of frozen-thawed buffaloepididymal spermatozoa were studied in comparison to ejaculated ones. Storage thermal resistance were significantly (P
Keywords: Epididymis spermatozon; thermal resistance; buffalo bull; freezing; thawing spermatoza